Detachment of the choroid after strabismus surgery in high myopia - Gawęcki, Maciej; Gębka, Andrzej; Raczyńska, Krystyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
We present a case of 60 years old woman, who underwent strabismus surgery due to cosmetically disturbing large divergent strabismus. Before surgery we found exotropia of the LE of 40 PD with hypotropia of 15 PD. Patient had surgery of convergent strabismus on this eye in childhood. LE was amblyopic since childhood, BCVA = 1/50, with moderate axial myopia and astigmatism (-2.75/ -2.0 ax 165). We performed lateral rectus recession of 8 mm and medial rectus anteposition of 2 mm with simultaneous vertical transposition of these muscles 7 mm upwards. Despite special attention during scleral pass of the needle due to thin myopic sclera, a single microperforation occurred, followed by seemingly insignificant vitreal flow. On the next day after surgery horizontal orthoposition was achieved with reduction of hypotropia to 7 PD. However, we found small vitreal hemorrhage and significant retinal folding. On USG exam we found large choroidal detachment in all quadrants. As there was possibility of simultaneous retinal detachment, patient was hospitalized in Department of Ophthalmology of Medical University of Gdańsk, where conservative treatment was applied and retinal detachment excluded. Four weeks after surgery complete choroidal attachment was achieved.